The Quality of Life of a Teenager with Rasmussen’s Encephalitis — Case Report - Marta Lewicka; Ewa Barczykowska; Bogumiła Małecka; Ewa Kontna (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Rasmussen’s Syndrome (RE), is a rare type of chronic focal encephalitis (CFE) of unexplained etiology and progressive course. It is characterized by resistant to treatment epileptic seizures. Mainly, these are epilepsy partialis continua (EPC) seizures. In the course of the disease, regress of cognitive function and progressive neurological deficits follow, primarily, hemiparesis. Quality of life examination is an expression of a holistic approach towards the patient. These studies are really important in the chronic diseases. Apart from the time of survival, they may be the dependent variable in the models of, treatment effectiveness of and care assessment. Case Report. The case study concerns a 15- year-old sick girl, whose neurological condition, has been steadily deteriorating — aphasia and dementia dominate, hemiparesis is low. The assessment of the quality of the patient’s life was assessed by the pediatric quality of life questionnaire (PedsQL 4.0) Discussion. Subjective assessment of the quality of life assessed by the patient, is a source of information, which is often different from the assessment made by the girl’s mother. Furthermore, subjective evaluation suggests for existence of patient’s needs that are imperceptible, which require professional care and assistance outside the hospital environment. Conclusions. The patient with RE is characterized by complexity and a multitude of health problems. According to the assessment made by the girl the quality of her life is lower compared to the answers given by the mother. (JNNN 2018;7(1):33–39)